Method of Teaching Arabic in Madrasah Tarbiyah Islamiyah Koto Panjang Lampasi Payakumbuh - Sumin, Syar'i (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Methods of teaching Arabic and their innovations will be a challenge for any teachers of Arabic. Therefore, teaching Arabic will also require the intelligence of each teacher to understand the aspects related to learning outcomes, namely by creating new techniques in teaching Arabic language so that students become more active, skillful, able to master and proficient Arabic. Boarding school of Madrasah Islamiah Tarbiyah Koto Panjang Lampasi has proven itself as the school of giving motivation, and innovation in the development of generations of people who have been able to reach the highest point of improvement, both in quantity and in quality of the students’ achievements. The method used in this research is qualitative descriptive which describes methods of teaching Arabic at MTI Koto Panjang Lampasi Payakumbuh. The source of the data of this research is the teachers, students, the foundations, and community. The technique of collecting data obtained from various teachers who taught Arabic at MTI through interviews and observations. The results showed that there are 10 steps of Arabic language learning method applied in MTI Koto Panjang.